Framing and feelings on social media: the futures of work and intelligent machines - Ocal, Ayse; Crowston, Kevin (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeResearch on artificial intelligence (AI) and its potential effects on the workplace is increasing. How AI and the futures of work are framed in traditional media has been examined in prior studies, but current research has not gone far enough in examining how AI is framed on social media. This paper aims to fill this gap by examining how people frame the futures of work and intelligent machines when they post on social media.Design/methodology/approachWe investigate public interpretations, assumptions and expectations, referring to framing expressed in social media conversations. We also coded the emotions and attitudes expressed in the text data. A corpus consisting of 998 unique Reddit post titles and their corresponding 16,611 comments was analyzed using computer-aided textual analysis comprising a BERTopic model and two BERT text classification models, one for emotion and the other for sentiment analysis, supported by human judgment.FindingsDifferent interpretations, assumptions and expectations were found in the conversations. Three subframes were analyzed in detail under the overarching frame of the New World of Work: (1) general impacts of intelligent machines on society, (2) undertaking of tasks (augmentation and substitution) and (3) loss of jobs. The general attitude observed in conversations was slightly positive, and the most common emotion category was curiosity.Originality/valueFindings from this research can uncover public needs and expectations regarding the future of work with intelligent machines. The findings may also help shape research directions about futures of work. Furthermore, firms, organizations or industries may employ framing methods to analyze customers' or workers' responses or even influence the responses. Another contribution of this work is the application of framing theory to interpreting how people conceptualize the future of work with intelligent machines.
Keywords: Technology; Computer-supported collaborative work (CSCW); Social media; Content analysis; Human-computer interaction (HCI); Social computing; Text analysis; INFORMATION-TECHNOLOGY; ACCEPTANCE; EMOTIONS; FRAMES; SENSE; Information Science & Library Science